Reactivity and Selectivity of Iminium Organocatalysis Improved by a Protein Host. (23rd August 2018) - Nödling, Alexander R.; Świderek, Katarzyna; Castillo, Raquel; Hall, Jonathan W.; Angelastro, Antonio; Morrill, Louis C.; Jin, Yi; Tsai, Yu‐Hsuan; Moliner, Vicent; Luk, Louis Y. P.
Abstract: There has been growing interest in performing organocatalysis within a supramolecular system as a means of controlling reaction reactivity and stereoselectivity. Here, a protein is used as a host for iminium catalysis. A pyrrolidine moiety is covalently linked to biotin and introduced to the protein host streptavidin for organocatalytic activity. Whereas in traditional systems stereoselectivity is largely controlled by the substituents added to the organocatalyst, enantiomeric enrichment by the reported supramolecular system is completely controlled by the host. Also, the yield of the model reaction increases over 10‐fold when streptavidin is included. A 1.1 Å crystal structure of the protein–catalyst complex and molecular simulations of a key intermediate reveal the chiral scaffold surrounding the organocatalytic reaction site. This work illustrates that proteins can be an excellent supramolecular host for driving stereoselective secondary amine organocatalysis.